2021
DOI: 10.3390/vaccines9121506
|View full text |Cite
|
Sign up to set email alerts
|

Mycoplasma suis Alpha-Enolase Subunit Vaccine Induces an Immune Response in Experimental Animals

Abstract: Recombinant protein technology has emerged as an excellent option for vaccine development. However, prior to our study, the immune induction ability of recombinant Mycoplasma suis alpha-enolase (rMseno) in animals remained unclear. The purpose of this study was to develop a rMseno protein subunit vaccine and to determine its ability to elicit an immunological response. To accomplish this, we cloned the gene into pET-15b, expressed it in BL21 cells, and purified it. Following the establishment of immunity, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…In mice, immunizations with rMseno caused increased levels of IFN-γ and IL-4 cytokines and increased the T lymphocyte proliferation index [90]. Meanwhile, in piglets, the results showed an increased level of specific IgG1, IgG2a, CD4, and CD8 cells [90]. A study by Téllez-Martínez et al ( 2019) [91] demonstrated that BALB/c mice, immunized with enolase-based vaccine and Montanide PetGel A (PGA) as an adjuvant, demonstrated a strong specific Th1 response and protective immunity against Sporothrix schenckii.…”
Section: Enolasementioning
confidence: 99%
See 2 more Smart Citations
“…In mice, immunizations with rMseno caused increased levels of IFN-γ and IL-4 cytokines and increased the T lymphocyte proliferation index [90]. Meanwhile, in piglets, the results showed an increased level of specific IgG1, IgG2a, CD4, and CD8 cells [90]. A study by Téllez-Martínez et al ( 2019) [91] demonstrated that BALB/c mice, immunized with enolase-based vaccine and Montanide PetGel A (PGA) as an adjuvant, demonstrated a strong specific Th1 response and protective immunity against Sporothrix schenckii.…”
Section: Enolasementioning
confidence: 99%
“…There are only studies of enolase from different organisms to be found. In a study by Xue et al (2021) [90] mice and piglets were immunized using recombinant Mycoplasma suis alpha-enolase (rMseno). In mice, immunizations with rMseno caused increased levels of IFN-γ and IL-4 cytokines and increased the T lymphocyte proliferation index [90].…”
Section: Enolasementioning
confidence: 99%
See 1 more Smart Citation
“…For example, DnaK from Mycoplasma hyopneumoniae and Mycoplasma ovipneumoniae elicits strong humoral and cellular immune responses ( 24 , 25 ). In Mycoplasma suis and Streptococcus suis , the enolase induces a robust immunological response and provides protective efficacy ( 26 , 27 ). Mice immunized with EF-Tu subunit vaccines are protected from Streptococcus suis or Streptococcus pneumoniae challenge ( 28 , 29 ).…”
Section: Introductionmentioning
confidence: 99%
“…Because of safe, cost-effective and efficacious, subunit vaccine has promising applications compared to other vaccines. In recent years, the development of subunit vaccines has been carried out in other mycoplasma diseases 6,7 . Subunit vaccine has been extremely difficult to acquire due to the lack of understanding of M. synoviae proteins.…”
Section: Introductionmentioning
confidence: 99%